Efficiency of Contractual Arrangements in Private Agricultural Product Markets - Boyd, Haleigh; Evans, Lewis; Quigley, Neil (Victoria University of Wellington Law Review, 2000)
The electronic and information revolution is changing virtually all aspects of economic and social life, no more so than in the ability of firms of all sizes to make their mark in production and exporting. The ready access to vast information and the lower costs that now attend dealing with other firms have opened opportunities that never before would have been cost-effective at the individual firm level. These firms have to contract with other firms for all sorts of purposes. Because of the small size of agricultural and horticultural producers and special problems of seasonal production, variability in production and price, and product perishability, some of the most challenging contracts are in this sector. Co-operatives provide a vehicle for the vertical integration of production and processing in agriculture. The producers provide capital for and control the processing entity so that their interests are aligned. Returns to producers bundle together the commodity price and the return from the capital invested in processing. Many of the agricultural product markets in New Zealand operate within this co-operative structure, and in the case of the dairy industry, it is supported by statute. The forestry, wine and processed vegetable industries are notable exceptions in that these industries employ contracts between producers and processors as an alternative to vertical integration via co-operatives. In this article, we use examples of contracts between producers and processors in the forestry, wine and processed vegetable markets to consider the extent to which contracts may provide efficient vehicles for the alignment of interests between producers and processors in agricultural markets. We consider the ways in which these contracts: •Minimise transaction costs; •Use incentive mechanisms and monitoring to limit opportunism; •Allocate risk; •Facilitate investment in specific assets; and •Allocate property rights. We assess the implications of the annual crop cycles and perishability of grapes and vegetables with the longer crop cycles of forestry. We conclude that contracts appear to be viable alternatives to co-operative structures, even in the market for perishable agricultural products.